ANALISIS PENGARUH FRAUD PENTAGON THEORY TERHADAP FRAUDULENT FINANCIAL REPORTING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2019 - Widyatama, Whisnu; Setiawati, Loh Wenny (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2020)
Fraudulent financial statements or fraudulent financial reporting are actions that cause a person or group of people to obtain certain benefits at the expense of other parties. Fraudulent financial statements themselves are the biggest cause of loss in the world. Therefore, financial statements that are not presented reliably and are not honestly disclosed can mislead users in making economic decisions. This study aims to analyze the effect of pentagon theory fraud proxied by five variables, that are CEO duality, change of board of directors, number of independent commissioners, level of leverage, and change of auditors to fraudulent financial reporting proxied by Beneish M-Score in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. This study uses 205 observational data using logistic regression analysis. The results of this research indicate that CEO duality and the change of board of directors have a significant effect on fraudulent financial reporting, while the number of independent directors, the level of leverage, and the change of auditors do not affect fraudulent financial reporting.